Akumulacja ludzi, akumulacja kapitału. O splocie kapitalizmu i biopolityki na przykładzie nowoczesnej urbanizacji = Accumulation of capital and people. Linking capitalism and biopolitics in the process of modern urbanisation - Swianiewicz, Jan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt at capturing the process of modern urbanisation in terms of Michel Foucault`s theory of power technologies. Drawing on the charateristics of urban forms corresponding to three techniques of power constitutive to modern Western societies (sovereignty, discipline and government), as presented by Foucault in the 1977/78 series of lectures entitled "Sécurité, territoire, population", the author argues that urbanisation viewed from this perspetive turns out to be a process of the accumulation of people, losely linked and parallel to the process of capital accumulation.
Keywords: urbanizacja; kapitał; ludzie; biopolityka